Curiosity: Art and the Pleasures of Knowing - Colin Sterling (Opticon1826, 2014)
Colin Sterling's review of the exhibition Curiosity: Art and The Pleasures of Knowing at the Turner Contemporary won the first prize in the UCL Graduate School Review Competition 2013/2014.